An estimate of Thermal Comfort at some stations in India - VENKITESHWARAN, SP; SWAMINATHAN, MS (MAUSAM, 1967)
The paper describes briefly how the thermal aspect influences comfort. Since comfort depends not only on the temperature of the air, but also on the relative humidity and air movement, no simple formula to obtain an index involving all the factors is available. In this paper Thorn’s simple empirical formula for a Discomfort Index =0.4(td +tw )+15, where td is air temperature and tw is the wet bulb temperature, is used and the mean hourly values of discomfort index are calculated for different months for the 5 stations, New Delhi, Calcutta, Poona, Madras and Trivandrum. According to Thom, people in the U.S.A., feel discomfort as the index rises above 70 and everyone is uncomfortable by the time the index reaches 79. When the index becomes 86 or higher, in Washington metropolitan area, mass dismissal of employees are permitted. The analysis of Indian data shows that in general, the prevailing DI for India is in the range 76-80 or less, except in the summer months, April-May to September, when it exceeds this value. Poona has the largest number of hour days with DI = or <75. In the range Dl= 76-80, Poona and Trivandrum have the largest and almost similar values, viz., 8224 and 8343 hour days respectively but a possible total of 8760 during the year. Dl = 86-90 is experienced in the pre-monsoon months only in New Delhi (368 hour-days), Calcutta (183) and Madras (239). It is generally observed that the indices can be adopted for the tropical Indian conditions also. They will, therefore, be of value to visitors from abroad and to the Indians. They will also be useful to plan, air conditioning units for Indian use.